SUBACULAR SCLEROZING PANENCEPHALITIS IN CHILDREN AND PALLIATIVE CARE - Saidazizova Sh.X.; Sattorov S.Sh; Inomov F.U (Western European Studies, 2026)
Subacute sclerosing panencephalitis (SSP) is a progressive and often fatal neurodegenerative disease that occurs as a result of long-term persistence of the measles virus in the central nervous system (CNS). SSP is mainly observed among children and adolescents, the onset of the disease often occurs years after measles. Currently, there is no specific curative therapy; Antiviral agents (inosiplex, interferon), immunomodulators, and symptomatic therapy may slow the progression of the disease or provide temporary remission in some patients, but the main approach is to provide comprehensive palliative and rehabilitation care. This article reviews the epidemiology, etiopathogenesis, clinical presentation, paraclinical diagnostics, and especially the principles of palliative treatment and rehabilitation appropriate to the stages of OSA. The article concludes with practical recommendations and future research directions. (NCBI)
Keywords: OSA; measles; palliative medicine; rehabilitation